PSXI-14 Enteric methane and nitrogen emissions in cattle consuming tanniferous and non-tanniferous legumes, grass or a ration. (8th October 2021) - Villalba, Juan J; MacAdam, Jennifer; Guevara, Raul
Abstract: Incorporation of legumes into forage systems has been a widely adopted strategy to increase pasture productivity and forage nutritive value, while reducing N inputs. In addition, some legumes contain beneficial chemicals like condensed tannins (CT), which could enhance the efficiency of energy and protein use in ruminants relative to other forages. We assessed (i) animal performance, (ii) methane emissions (SF6 technique), and (iii) concentration of nitrogen in urine and blood in cattle grazing a CT-containing legume (birdsfoot trefoil; BFT), a legume without tannins (cicer milkvetch; CMV), a grass (meadow brome; MB), or in cattle fed a total mixed ration (TMR). Fifteen Angus heifers were randomly assigned to one of three treatment pastures: (1) BFT, (2) CMV, and (3) MB. Each treatment had 5 spatial replications, randomly divided into three paddocks (64 × 57m), seeded with BFT, CMV or MB, and one heifer was assigned to each paddock. Five Angus heifers were randomly assigned to individual adjacent pens and received a TMR ration (25% of alfalfa hay, 25% corn silage and 50% chopped barley) during the same period. Response variables were analyzed as a split-plot design, with experimental units as the random factor and treatment as a fixed factor with day as the repeated measure. Cows grazing BFT (1.9% condensed tannins) or fed the TMR showed greater weight gains than cows grazing CMV or MB (P = 0.0006). Methane emissions did not differ among treatments (P > 0.05; Table 1). Blood urea nitrogen concentrations were similar in cows grazing BFT or CMV (P = 0.1202), but greater than in animals grazing MB or fed TMR (P < .0001). Urinary nitrogen concentrations were similar among treatments (P = 0.5266). These results suggest grazing tanniferous legumes enhanced BW gains with similar methane and urinary nitrogen emissions to grass and confinement alternatives and greater levels of production than grass or CMV.